Business environment - Fernando, A. C. (Pearson, 2011)
Managers need to need to keep abreast of the latest economic developments in countries around the world, and use this information to analyse and correlate with the economic environment in which businesses function to be able to make informed decisions that will enable the organization to progress despite obstacles. A course in business environment fosters this ability and in Business Environment A. C. Fernando integrates concepts with real-world situations and the most recent data to help students grasp complex economic concepts, a clear understanding of which is required to comprehend the various facets of business environment. He adopts a jargon-free style and presents the subject matter logically, from elementary to complex concepts to engage the student completely. Divided into eight parts comprising fifty chapters, the book has been designed to be of particular use to students who are not familiar with the concepts of economics.